Numerical Taxonomic Evaluation of Leaf Architectural Morphology of Vitex L. species (Lamiaceae Martinov) in Peninsular Malaysia - Md Zin, Syanawiyyah; Mohamed, Fatimah; Mohd Noor, Nor Nafizah (Journal of Science and Mathematics Letters, 2022)
A numerical taxonomic is an algorithm method that is used to evaluate scored characters of continuous characters such as leaf architectures. Leaf architecture characters were scored from 11 Vitex species in Peninsular Malaysia (V. gamosepala, V. glabrata, V. longisepala, V. millsii, V. negundo, V. pinnata, V. quinata, V. trifolia, V. vestita, Vitex sp.1 and Vitex sp.2), one subspecies (V. trifolia subsp. litoralis) and two varieties (V. negundo var. bicolor and V. negundo var. cannabifolia) were investigated using herbarium voucher specimens and fresh specimens collected from the fieldwork. Species collected were from Pasoh Forest Reserve, Negeri Sembilan; Gunung Lambak Forest Reserve, Johor; Sungai Dara Forest Reserve, Perak; Proton City, Tanjong Malim, Perak; Gunung Lambak Forest Reserve, Johor; Cameron Highland, Pahang; Herb Walk Garden, Langkawi; and Kg. Pulau Belanga, Kota Bharu, Kelantan. All the studied Vitex species shared leaf architecture as follow: arrangement (opposite), marginal ultimate (looped), position of petiole arrangement- P.O.P.A (marginal) and petiole feature (swollen base). Specimens with single leaf type and presence of petiolule further help in distinguishing Vitex species. The scored data were analysed using Multi-Variate Statistical Package (MVSP) and Phylogenetic Analysis Using Parsimony (PAUP) softwares to obtain similarity values between species and their evolutionary relationship, respectively. Dendogram clades show an overall Gower General Similarity Coefficient (GGSc) value at 0.715 to 0.964 which indicate clear separation at genus and species level while pairwise distance between the in-group and out-group taxa analysed in the neighbour-joining tree was in between 0.26364 to 0.55455 showing that trees were constructed with strong bootstrap support with Consistency Index (CI) 0.6852 (CI) excluding uninformative character = 0.6000, Homoplasy index (HI) 0.3148 (HI excluding uninformative character = 0.4000), Retention Index (RI) 0.5802 and rescaled consistency index (RC) 0.3976. As a conclusion, high similarity in leaf architecture characters of all 11 species, one subspecies and two varieties of Vitex studied in Peninsular Malaysia suggest and support them belongs to the same genus hence supporting the taxonomic significance. This study implicate that leaf architecture morphological characters of vegetative parts can be used in identification to species, subspecies and variety level of this genus and might propose some changes to the placement of taxa hence can be devoted as an improvement for the previous Vitex study.